EFFICACY OF LOGO INSTRUCTIONAL PACKAGE ON DIGITAL COMPETENCY SKILLS OF LOWER PRIMARY SCHOOL IN OYO STATE, NIGERIA (Unilorin Journal of Lifelong Education, 2025)
The lower primary classes (Primary I to III) are last part of early years education which is known as the foundation phase of basic education in Nigeria. This level of education is meant to prepare the pupils for the fundamental skills and knowledge required not only for further education but for successful living in the 21st century and beyond, hence the introduction of Basic Science and Technology. But the extent to which pupils in public lower primary schools, exposed to the digital skills and knowledge in Nigeria is in question. Based on this, this study exposed primary school pupils to programming using the Language of Graphics Orientation (LOGO) and measured their digital competence in it. The developed LOGO Instructional Package (LIP) through action research and implemented the package adopting a one-group pretest-posttest quasi-experimental design. Due to experimental mortality, 349 pupils fully completed the study, which cut across ages 5+, 6+, 7+ and 8+ years from four schools. Data were collected using a self-designed LOGO Programming Achievement Test (r = 0.70) and Computer Literacy Scale (á = 0.72). Descriptive statistics, graphs, t-tests, and Pearson product-moment correlation (PPMC) were used to analyse the data. Pupils at age 6 had competence in modules 6, 7 and 9 (Which deals with the command window, the input box and turtle to draw and saving works respectively) with a mean ranging from 2.77 to 4.36 (6.0 being the mark obtainable) among other results. Computer skills should be made compulsory in primary schools.